2018
DOI: 10.1161/hypertensionaha.118.10911
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management of Postnatal Hypertension

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02333240.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 27 publications
0
100
0
Order By: Relevance
“…The same research team subsequently published results of a feasibility trial of women’s self-management of BP 29. Ninety-one (49%) of 186 women approached from 5 NHS units who had gestational hypertension or pre-eclampsia which required postnatal antihypertensive management were recruited and randomised to self-management (n=45) or usual care (n=46).…”
Section: Resultsmentioning
confidence: 99%
“…The same research team subsequently published results of a feasibility trial of women’s self-management of BP 29. Ninety-one (49%) of 186 women approached from 5 NHS units who had gestational hypertension or pre-eclampsia which required postnatal antihypertensive management were recruited and randomised to self-management (n=45) or usual care (n=46).…”
Section: Resultsmentioning
confidence: 99%
“…A pilot RCT (SNAP-HT) was conducted in women with hypertensive disorders of pregnancy (HDP) postpartum, comparing a novel self-management intervention, comprising HBPM with self-adjustment of antihypertensive medication supported by telemonitoring, with usual care (1). Women aged ≥18 years, with gestational hypertension or pre-eclampsia, requiring antihypertensive treatment, were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Contribution to the literature In the randomised trial, those self-managing had consistently lower diastolic blood pressure to six months postpartum (1). This mixed methods study provides compelling adjunctive information about possible explanations for the success of self-management;…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite its importance, there is limited evidence to support how to use antihypertensive therapy postpartum 27 . One trial found that HBPM and postnatal down-titration of antihypertensives improved BP control 28 . The most commonly used antihypertensives, and most others, are acceptable for use when breastfeeding 29 .…”
Section: Measure Bp Postpartum On Days 3-6 After Hypertensive Pregnancymentioning
confidence: 99%